Determination Coal Mine Ultimate Pit Limit based on Kepmen ESDM No. 227.K/MB.01/MEM.B/2023 and PP 26 2022 - Suparno, Fanteri Aji Dharma; Aminah, Siti; Haeruddin, Haeruddin; Lestari, Rina; Mulyani, Kurnia Dewi; Manek, Emanuel; Sulistyo Rini, Utari Retno (Journal of Earth and Marine Technology (JEMT), 2025)
Economic factors and variables from geological resource models affect ultimate pit limit (UPL). Coal selling price, overburden stripping cost, coal mining cost, and royalties are among the economic factors taken into account in UPL. PP 26 2022 and Kepmen 227.K/MB.01/MEM.B/2023 both control the benchmark coal selling price and royalties. It takes a lot of time to determine UPL utilizing the Lerchs Grossman (LG) algorithm. UPL optimization is now feasible by integrating mining modelling software's Structured Query Language (SQL). The goal of this study is to determine UPL by maximizing coal resources at the site using the help of SQL in LG algorithm, which can optimize pits efficiently, precisely, and economically while taking the most recent laws into account. The study investigates a coal mine in Sanga-sanga, East Kalimantan. The study entails examining data processing using secondary data that was gathered for the study. Using the break-even stripping ratio (BESR) analysis approach, mining limitations are chosen. The chosen incremental stripping ratio (ISR) of 12.88 is in close proximity to the $13.41/ton break-even stripping ratio (BESR). The grid OPT015 in the optimization grid contains the incremental stripping ratio (ISR) value and considered as the UPL for the coal mine.